PELATIHAN HYPNOBIRTHING BASIC UNTUK MANAJEMEN NYERI PERSALINAN PADA IBU HAMIL DI DESA TARAWEANG, KECAMATAN LABBAKKANG, KABUPATEN PANGKEP, PROPINSI SULAWESI SELATAN - Syam, Azniah; Dewi, Indra; Nurbaya, Sitti; Fajriansi, Andi (LPPM Institut Pendidikan Nusantara Global, 2024)
Hypnosis, self-hypnosis, and hypnobirthing are techniques to overcome childbirth anxiety. Expectant mothers are taught to trust their bodies, regain confidence in their ability to give birth, and release tension and pain through deep relaxation, breathing, and visualization techniques. Despite the many relevant studies cited, hypnobirthing has not been an institutionally preferred option offered by childbirth service providers such as government health centers and hospitals, possibly due to a lack of written policy support. This option is available through private childbirth service providers or hypnobirthing practitioners who provide complementary therapies. The lack of comprehensive childbirth preparation (physical, mental, and social) among young mothers in Taraweang Village, Labbakkang Sub-district, Pangkep District This prompted us to present a new approach to childbirth by introducing the concept, benefits, and how to do self-hypnosis independently to increase awareness and readiness before birth. This activity was implemented on April 5, 2023, after a socialization process with the partners in March 2023. The activity, which involved 15 pregnant women from Taraweang Village, began with a screening process for labor readiness and the mother's mental health condition using a distress scale form. Then followed socialization and training, as well as a 60-minute hypnosis simulation using reclusiveness techniques to increase awareness and readiness for dealing with pain. The activity ended with a pre-test to assess the mother's reaction to the therapy results. Based on data analysis, we concluded that pregnant women who received 60 minutes of hypnobirthing relaxation therapy experienced a decrease in the distress scale. This activity is expected to be carried out independently at the mothers' homes using the knowledge that has been provided in the process of community partnership activities in 2023. This activity will be further developed and evaluated, especially to ensure the sustainability of the benefits felt by partners in subsequent activities.